2020
DOI: 10.1111/anae.15055
|View full text |Cite
|
Sign up to set email alerts
|

The effect on consent rates for deceased organ donation in Wales after the introduction of an opt‐out system

Abstract: Summary Organ transplantation saves and transforms lives. Failure to secure consent for organ retrieval is widely regarded as the single most important obstacle to transplantation. A soft opt‐out system of consent for deceased organ donation was introduced into Wales in December 2015, whilst England maintained the existing opt‐in system. Cumulative data on consent rates in Wales were compared with those in England, using a two‐sided sequential procedure that was powered to detect an absolute differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 15 publications
0
45
0
2
Order By: Relevance
“…35 For example, the upward trend in the proportion of families consenting to donation after brain death in Wales as compared with England reached statistical significance 33 months after the Welsh law change. 36 However, this increase in consent has not been reflected in the quarterly donation figures reported. 35,36 This may be because there has been lower eligibility for organ donation since the legislative change; or perhaps the law change in Wales has not yet had enough time to make an impact.…”
Section: What Can We Expect To Happen In England Based On a Similar Rmentioning
confidence: 98%
See 2 more Smart Citations
“…35 For example, the upward trend in the proportion of families consenting to donation after brain death in Wales as compared with England reached statistical significance 33 months after the Welsh law change. 36 However, this increase in consent has not been reflected in the quarterly donation figures reported. 35,36 This may be because there has been lower eligibility for organ donation since the legislative change; or perhaps the law change in Wales has not yet had enough time to make an impact.…”
Section: What Can We Expect To Happen In England Based On a Similar Rmentioning
confidence: 98%
“…36 However, this increase in consent has not been reflected in the quarterly donation figures reported. 35,36 This may be because there has been lower eligibility for organ donation since the legislative change; or perhaps the law change in Wales has not yet had enough time to make an impact. Any complex behaviour change intervention such as this requires public and professional buy-in, both of which can be influenced by the way in which the media presents information.…”
Section: What Can We Expect To Happen In England Based On a Similar Rmentioning
confidence: 98%
See 1 more Smart Citation
“…Deemed (presumed) consent and authorisation legislation will soon be in every nation of the UK, bar Northern Ireland. Statistical analysis carried out by NHS Blood and Transport (NHSBT), comparing the impact of deemed consent in Wales with England demonstrated that consent for DCD did not reach statistical significance, unlike DBD [27]. The authors speculated that DCD was less influenced by the legislation change due to differing family experiences of the two types of donation.…”
Section: The Future Of Dcd In the Ukmentioning
confidence: 99%
“…As in Nova Scotia, consent model reform is typically introduced as part of a broad healthcare system transformation, making it difficult to determine the isolated impact of deemed consent. 7 While some jurisdictions, including recent data from Wales, have shown a positive impact on donation rates with deemed consent systems, 8 another report analyzing data from 35 developed countries found no significant difference between the rates of donors per million population in countries with or without a deemed consent model. 7 Other studies have reported neutral and potentially negative impacts in the short-term, particularly on living donor rates.…”
Section: Introductionmentioning
confidence: 99%